The Examination of Reporting Channel Under Structural and Reward Model of Whistleblowing: An Experimental Approach - CAESAR MARGA PUTRI (The Indonesian Journal of Accounting Research, 2013)
The objective of this research is to examine empirically the effectiveness of two different whistleblowing models (structural vs reward) in encouraging people to report wrongdoing or fraud. To achieve the objective, this study employs an experiment method, with 55 participants from two universities. The result shows that an anonymous channel under the structural model is more effective than a non-anonymous channel. Additionally, this study finds that the non-anonymous channel in the reward model is more effective than the anonymous channel.